Stability of attachment styles across students’ romantic relationships, friendships and family relations - Kamenov, Željka (Array, 2005)
Research on adult attachment focused mainly on the relationship with partners. However, attachment theory predicts that attachment style once formed in childhood defines the structure and quality of later relationships to significant others, which means not only partners, but also friends and family members. We were interested in finding out whether the type of relationship is a relevant variable and whether the incidence of a particular attachment style differs with regard to the type of close relationship. The aim of our study was to assess the stability of attachment styles across students’ romantic relationships, friendships and family relations. The sample consisted of 210 male and female undergraduate students of the University of Zagreb. The Experiences in Close Relationship Inventory developed by Brennan et al. (1998) was administered to the participants. In order to assess the level of attachment toward other objects (friends and family members), the instrument was slightly modified. Data were analysed and interpreted both according to their position on attachment dimensions and the type of attachment they indicate. The results show that people form a more secure attachment in their relations with members of their families and friends than with their romantic partners. We investigated whether there is a correspondence between attachment styles in different types of close relationships. The only style that appears relatively stable is secure attachment. The non-secure attachment styles with romantic partners are highly compensated for with the secure one in other, less threatening relationships, with friends or family members. The results are discussed in relation to the age of participants and the characteristics of students’ life-style.